PREVALENCE OF VITAMIN D DEFICIENCY AND ITS RELATIONSHIP WITH SUBCLINICAL HYPOTHYROIDISM - SUDHA K; ANUPAMA HEGDE; POORNIMA A MANJREKAR; RESHMA KUMARCHANDRA (International Journal of Pharma and Bio Sciences, 2013)
Vitamin D deficiency has been implicated in various diseases including cancer and auto immune diseases. The present study attempts to establish a relation between vitamin D deficiency, thyroid hormones and TSH in subclinical hypothyroidism.100 newly diagnosed patients with subclinical hypothyroidism were divided into three groups according to vitamin D levels. Mean plasma TSH and T3 values decreased with increasing vitamin D values and T4 increased with increasing vitamin D tertiles. However , intergroup comparison showed no statistically significant changes .In females, negative correlation between vitamin D and TSH was statistically significant (p=0.014).The prevalence of vitamin D deficiency, insufficiency and sufficiency in 100 patients was found to be 38%, 38% and 24%. The study indicates the prevalence of vitamin D deficiency in subclinical hypothyroidism, but further studies are needed to determine whether it is a causative factor in the pathogenesis of the disease or a consequence.